Perbedaan Model Pembelajaran Project based Learning dan Model Konvensional terhadap Kemampuan Berpikir Kreatif Siswa Kelas VII SMPN 1 Wirosari - Siti Nurkhasanah; Chientya Annisa Rahman Putrie (Neolectura, 2023)
The background in this study is that students' creative thinking skills are still low. In carrying out the process of teaching and learning activities in keals still use conventional methods. This study aims to determine the difference between the project-based learning model and the conventional model on the creative thinking skills of class VII students of SMPN 1 Wirosari. This type of research method uses a quasi-experimental research type, namely the posttest only group design model. The population in this study consisted of 288 students, samples taken in class VII.A and VII.B with a total of 64 students. Data collection techniques through observation, documentation and test tests with essay questions which are carried out at the end of learning. Then processing the data that has been collected is processed through validity tests and reliability tests. Based on the results of the normality and homogeneity tests, the test results obtained for both normal and homogeneous groups were 97.67667. So to test the hypothesis with the t-test, the two samples are not correlated.